Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1089/acm.1996.2.345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Honey versus Thyme on Rubella Virus Survival in Vitro

Abstract: In this paper, we assess the antiviral properties of honey solutions and thyme extracts at varying concentrations. This was done by testing these solutions in vitro using monkey kidney cell cultures that were infected with the Rubella virus. Our results indicated that honey had good anti-Rubella activity, while thyme did not. These results may justify the continuing use of honey in traditional medicines from different ethnic communities worldwide and in some modern medications such as cough syrups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 9 publications
2
47
0
1
Order By: Relevance
“…antibacterial [17], antiseptic [18], antiviral [19] and has widely been used to treat wounds. The honey has also been used to treat ulcers, burns, various inflammations [20,21] as well as antitumor potency [22].…”
Section: Introductionmentioning
confidence: 99%
“…antibacterial [17], antiseptic [18], antiviral [19] and has widely been used to treat wounds. The honey has also been used to treat ulcers, burns, various inflammations [20,21] as well as antitumor potency [22].…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of honey on infectious diseases was not investigated in the present study, previous studies have shown that honey exerts a wide range of antimicrobial activities, against various Gram-negative and Gram-positive human pathogenic bacteria and Candida albicans (Al-Waili & Saloom, 1999) as well as anti-leishmanial (Zeina et al, 1997) and antiviral activities (Herpes simplex (Al-Waili, 2004) and rubella virus (Zeina et al, 1996)). On the other hand, the effect of HBM on immune disorders may be supported by the study of Al-Waili (2001) which reported immunostimulatory effect of natural honey, by enhancing the antibody production against both thymus-dependent and thymusindependent antigens during primary and secondary immune responses.…”
Section: Resultsmentioning
confidence: 89%
“…[13] Honey was being conveyed and having preventive effects upon rubella virus activity. [100] Honey with reference to ophthalmology Sight and vision are vital, as they help humans to connect themselves with their surroundings, keep them safe, and also assist in maintaining the sharpness of minds. Apart from playing a significant role in curing numerous human ailments, honey has also been used in the treatment of innumerable ophthalmological disorders like chemical and thermal burns to eyes, keratitis, blepharitis, conjunctivitis, and corneal injuries.…”
Section: Honey In Primeval Greecementioning
confidence: 99%